Analisis Pengelolaan Wakaf Produktif dalam Efektivitas Pemberdayaan Sosial Ekonomi Masyarakat Kota Medan - Kausar, Al; Soemitra, Andri; Batubara, Chuzaimah (el Buhuth: Borneo Journal of Islamic Studies, 2023)
The purpose of this study was to examine and find out the management of waqf in an effort to effectively empower the socio-economic community of the city of Medan. The type of research used is field research (field research) with a qualitative descriptive approach which describes data and information based on data obtained in the field. In this case the author conducted a case study on 3 foundations, namely the H. Anif Foundation, the Al-Jihad Mosque Foundation , and the Ar-Raudatul Hasanah Foundation. The results of the research showed that the implementation of productive waqf management in Medan was a case study of 3 foundations, only 2 foundations had productive waqf and 1 still emphasized infaq and alms. 2 foundations that have productive endowments emphasize social and economic aspects.